Long-Term Clinical Impact of Intravascular Ultrasound Guidance in Stenting for Left Main Coronary Artery Disease. (20th October 2021) - Kang, Do-Yoon; Ahn, Jung-Min; Yun, Sung-Cheol; Park, Hanbit; Cho, Sang-Cheol; Kim, Tae Oh; Park, Sangwoo; Lee, Pil Hyung; Lee, Seung-Whan; Park, Seong-Wook; Park, Duk-Woo; Park, Seung-Jung
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Compared with angiographic guidance, intravascular ultrasound (IVUS)-guided percutaneous coronary intervention (PCI) is associated with better clinical outcomes. However, its very long-term clinical effect is still unclear in patients undergoing PCI for unprotected left main coronary artery disease. Methods: To compare 10-year outcomes of IVUS-guided versus angiography-guided PCI for left main coronary artery disease, we evaluated 975 patients who underwent unprotected left main coronary artery PCI between January 2000 and June 2006 from the MAIN-COMPARE (The Revascularization for Unprotected Left Main Coronary Artery Stenosis: Comparison of Percutaneous Coronary Angioplasty Versus Surgical Revascularization) registry. The 10-year rates of clinical outcomes (death; the composite of death, Q-wave myocardial infarction [MI], or stroke; and target-vessel revascularization) were compared between IVUS guidance and angiography guidance. Adjusted analyses were performed with the use of inverse-probability-treatment-weighting and propensity score matching. Results: Among the 975 patients, 756 (77.5%) had IVUS guidance. The observed 10-year incidence rate of death (16.4% versus 31.0%, P <0.001) and composite of death, Q-wave MI, or stroke (19.2% versus 32.9%, P <0.001) was significantly lower in the IVUS-guided than in the angiography-guided group. The 10-year incidence rate of target-vessel revascularization was similar between the 2 groups (21.8% versus 18.3%, P =0.41). After adjusting for potential confounders with inverse-probability-treatment-weighting, IVUS was associated with lower incidence of mortality (hazard ratio, 0.75 [95% CI, 0.55–1.03]; P =0.07) and composite of death, Q-wave MI, or stroke (hazard ratio, 0.79 [95% CI, 0.59–1.06]; P =0.11). In 208 propensity score–matched pairs, IVUS was also associated with lower incidence of death (hazard ratio, 0.73 [95% CI, 0.53–1.02]; P =0.07) and composite outcome of death, Q-wave MI, or stroke (hazard ratio, 0.71 [95% CI, 0.52–0.97]; P =0.03). The benefit of IVUS-guided PCI was consistent in the various subsets of clinical and anatomic characteristics. Conclusions: In patients undergoing PCI for unprotected left main coronary artery disease, IVUS-guided PCI compared with angiography-guided PCI was associated with lower long-term (10-year) risks of morality and composite of death, Q-wave MI, or stroke. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02791412.